Outcomes following the establishment of Qatar's quaternary neonatal general surgical service in a hospital with a "Tabula Rasa" for service development - Basem A Khalil; Abdalla E Zarroug; Abubakr Elawad; Saad Moussa; Collette Donnelly; Saleem Mammoo; Guy Brisseau; Alison Bedford Russell; Helmut Hummler (EL-Med-Pub, 2021)
Background: Sidra Medicine is the first dedicated Children and Maternity hospital in the State of Qatar. This paper describes the preparations for and results of activating quaternary neonatal surgical services in a brand new, "greenfield" hospital. We believe that these are the first published national results of neonatal general surgical services from the Gulf region. Methods: A review of surgical babies below four weeks corrected age from 1st of April 2018 - 31st of March 2020 was undertaken. Patient demographics, primary diagnosis, surgical procedures, 30-day postoperative mortality, overall mortality, and cause of death were recorded. Results: One hundred and sixty-nine babies (169) were identified (44.4% term and 55.6% preterm). Major surgery included laparotomy (76), congenital diaphragmatic hernia repair (20), surgery for anorectal malformations (25), and esophageal atresia (13). One set of conjoined twins were also separated successfully.  Fourteen babies died, resulting in overall mortality of 8.3 %. Excluding babies who died of life-limiting conditions, two babies died within 30 days of surgery, resulting in 30 days postoperative mortality rate of 1.2 %. Conclusions: The neonatal surgical mortality rate is comparable with those from top international centers. This low rate could be attributed to the high level of expertise preceded by months of preparations.